Analysis of Deixis in D4vd Song Lyrics Entitled “Here With Me” - Alvenius Zebua, Gifford; Silalahi, Charles; Ivanna Maybella Latupeirissa, Kezia (Green Publisher Indonesia, 2025)
This study examines the usage of deixis in D4vd’s song “Here With Me” (2022) using Stephen C. Levinson’s theory on three types of deixis: personal, temporal, and spatial. Pragmatics is a discipline of linguistics that studies how language functions in social contexts, taking into account speaker intentions, relationships, and situational circumstances. Deixis, as a critical element, necessitates contextual interpretation to determine meaning. The song lyrics were examined using a descriptive qualitative methodology to find instances of deixis. The findings show that personal deixis is most common, reflecting the speaker’s connection to the audience and the emotional undertone of the lyrics. Temporal deixis (and spatial deixis help to shape the song’s imagery and situational context. The study demonstrates how deixis improves knowledge of relationships, time, and place within the song, highlighting its significance in connecting language to context. These findings provide insights into how deixis functions in music and can help listeners perceive songs more efficiently.